Text Genres in Cardiac Emergency: from activity to typology - Ciapuscio, Guiomar Elena (Revista da ABRALIN, 2020)
Different lines and research traditions from contemporary Linguistics share an interest for text genres. The aims of this article are, firstly, briefly presenting some fundamental antecedents on the subject for Linguistics and reviewing the main research perspectives and traditions. Secondly, it intends to introduce conceptual developments elaborated within the German Text Linguistics (TL) framework, which in my opinion offer a global and explanatory vision of text genres. Thirdly, the article illustrates the corresponding theoretical aspects, based on a corpus of verbal interviews from an Argentine public hospital, during the treatment of cardiac emergencies. The analysis performed applies a qualitative methodology, which combines the conversational analysis methods (GÜLICH; SCHÖNDIENST; SURMANN, 2003; GÜLICH, 2007) in the case of oral data, and the methods of genre linguistics for the typologizing of texts (HEINEMANN, 2000; ADAMZIK, 2004; CIAPUSCIO, 2005). The theoretical-descriptive paper describes and addresses two complementary angles of analysis for text genre, developed within the TL framework: both as speakers’ communicative activities and theoretical-analytical instruments for the typologizing of texts.